119k views
2 votes
What is a quick and easy way to remember explicit and recursive formulas?

1 Answer

3 votes
I always found derivation to be helpful in remembering. Since this question is tagged as at the middle school level, I assume you've only learned about arithmetic and geometric sequences.

First, remember what these names mean. An arithmetic sequence is a sequence in which consecutive terms are increased by a fixed amount; in other words, it is an additive sequence. If
a_n is the
nth term in the sequence, then the next term
a_(n+1) is a fixed constant (the common difference
d) added to the previous term. As a recursive formula, that's


a_(n+1)=a_n+d

This is the part that's probably easier for you to remember. The explicit formula is easily derived from this definition. Since
a_(n+1)=a_n+d, this means that
a_n=a_(n-1)+d, so you plug this into the recursive formula and end up with


a_(n+1)=(a_(n-1)+d)+d=a_(n-1)+2d

You can continue in this pattern, since every term in the sequence follows this rule:


a_(n+1)=a_(n-1)+2d

a_(n+1)=(a_(n-2)+d)+2d

a_(n+1)=a_(n-2)+3d

a_(n+1)=(a_(n-3)+d)+3d

a_(n+1)=a_(n-3)+4d

and so on. You start to notice a pattern: the subscript of the earlier term in the sequence (on the right side) and the coefficient of the common difference always add up to
n+1. You have, for example,
(n-2)+3=n+1 in the third equation above.

Continuing this pattern, you can write the formula in terms of a known number in the sequence, typically the first one
a_1. In order for the pattern mentioned above to hold, you would end up with


a_(n+1)=a_1+nd

or, shifting the index by one so that the formula gives the
nth term explicitly,


a_n=a_1+(n-1)d

Now, geometric sequences behave similarly, but instead of changing additively, the terms of the sequence are scaled or changed multiplicatively. In other words, there is some fixed common ratio
r between terms that scales the next term in the sequence relative to the previous one. As a recursive formula,


a_(n+1)=ra_n

Well, since
a_n is just the term after
a_(n-1) scaled by
r, you can write


a_(n+1)=r(ra_(n-1))=r^2a_(n-1)

Doing this again and again, you'll see a similar pattern emerge:


a_(n+1)=r^2a_(n-1)

a_(n+1)=r^2(ra_(n-2))

a_(n+1)=r^3a_(n-2)

a_(n+1)=r^3(ra_(n-3))

a_(n+1)=r^4a_(n-3)

and so on. Notice that the subscript and the exponent of the common ratio both add up to
n+1. For instance, in the third equation,
3+(n-2)=n+1. Extrapolating from this, you can write the explicit rule in terms of the first number in the sequence:


a_(n+1)=r^na_1

or, to give the formula for
a_n explicitly,


a_n=r^(n-1)a_1
User TimJ
by
9.0k points

No related questions found